Comparative analysis of combined methylene blue photodynamic therapy and doxorubicin treatment of oral squamous cell carcinoma cell line: In vitro study on apoptosis - Shayan Momeni Goujani; Maryam Koopaie; Fateme Hamta Safarian; Neda Hakimiha; Shima Younespour (Photodiagnosis and Photodynamic Therapy)
Introduction: Squamous cell carcinoma (SCC) is the most common malignancy of the head and neck region. Combination therapy potentially enhances the effectiveness beyond that of each treatment alone. This study aimed to assess whether photodynamic therapy (PDT), using methylene blue as a photosensitizer in conjunction with doxorubicin, produces synergistic effects on the apoptosis of the oral squamous cell carcinoma (OSCC) cell line. Materials and methods: The human oral epidermal carcinoma cell line (KB cell line, NCBI Code: C152) was cultured in Dulbecco's modified Eagle's medium. Following at least 24 hours of incubation, the OSCC cells were distributed into six groups, with groups 1–3 and 5 performed in the dark to prevent any light interference. 1: control group; 2: treated with 3.2 μg/mL methylene blue; 3: exposed to various concentrations of doxorubicin; 4: PDT group (methylene blue + 660 nm light); 5: treated with both doxorubicin and methylene blue; and finally, 6: treated with PDT (methylene blue + 660 nm light) in conjunction with doxorubicin. Flow cytometry methods were used to assess apoptosis. Analysis of variance (ANOVA) was used to compare quantitative variables between groups, and Tukey's test was applied for pairwise group comparisons. Results: Flow cytometry analysis revealed that the highest level of cellular apoptosis occurred in the group treated with PDT in conjunction with doxorubicin. Conclusions: PDT using the photosensitizer methylene blue, in combination with doxorubicin, can serve as an effective agent for inducing apoptosis in OSCC cells.